Roda de conversa: (re)pensando o processo de ensino de alunos com deficiências no ensino fundamental II - Aporta, Ana Paula (Universidade Federal de São Carlos, 2019)
Research that aims to investigate the reality of the inclusive process of people with disabilities in the common school system points out several components that still represent a barrier to their effective quality. One of the most frequently portrayed components in the literature refers to the methodological issues contained in the teaching process of these students and the lack of training of teachers to work with this population in school. Thus, this research aimed to develop a continuing education with professionals responsible for Elementary School II, about curriculum adaptations to meet the student with disabilities included in their classroom. Thus, a qualitative research was conducted, of nature descriptive and outlined by action research. 23 professionals from the school community participated in the research, including: elementary school teachers; Brazilian Sign Language Interpreters - LIBRAS; speech therapist; pedagogical assistant; and instructors of children with disabilities in a School Unit in the interior of São Paulo State. As training and research procedure, formative conversations, observations of classroom activities and teachers' discourse analysis were carried out. Considering the applied nature of the research focus theme, observations were made from three classes of 6th grade teachers and records of activity adaptation practices before, during and after the conversation wheels. Wheel recordings were analyzed to identify the core components contained in teachers' statements that influence their practice. The results obtained in the first observations and then in the first two rounds of conversation, it was found that the teachers had difficulties to teach students with disabilities. Also, it was observed that teachers did not perform curricular adaptations in the activities aimed at teaching these students. After the first two rounds, teachers began to rework their own identities, and with that, they thought about activities options tailored for students with disabilities. Thus, it was observed that teachers had actions with the purpose of offering curricular learning considering the potentialities of students with disabilities. Moreover, at the end of the research, it was found that the conversation wheels contributed to adaptive actions for students with disabilities. With the observations of the teachers' classes after the wheels, it can be verified that they prepared and performed different activities based on the student's characteristics. Thus, this research states that the conversation wheel can be an effective teacher training strategy for changing the practice of teaching students with disabilities.
Conversation wheel: (re) thinking the teaching process of students with disabilities in middle school
Keywords: Educação especial; Inclusão; Formação continuada do professor; Adaptação curricular; Roda de conversa; Special education; Inclusion; Continued teacher training; Curriculum adaptation; Talk wheel; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO